(untitled) (International Journal of Biomedical Research, 2016)
Plasmonic Photo therapy (PPT) is a developing treatment modality for premalignant and malignant conditions. In this study, Gold nanospheres of 30 nm chose as potential sensitizer based on their pros and cons. Green Light Emitting Diode (LED) with 530nm of 30mW used as irradiation source. The cytotoxic effect of 30 nm GNPs based on the concentration and time was studied with MTT assay. In PPT, we study the cell death mechanism with non-coherent low power LED with GNP by photo irradiation study in Vero, Hela and Hep 2 cell lines. Post therapeutic changes in normal Vero and malignant Hela and Hep 2 cell lines were also observed for 2 ,24 and 48 hours. We observed localized apoptotic/secondary necrosis in irradiated spot, leading to irreversible cell. The viability and cell division of non-irradiated cells around irradiated spot was observed microscopically and by MTT assay. In PPT, fluence and GNP concentration were optimized since they perform crucial role in the mode of cell death. In this study we hypothesized that; plasmonic phototherapy leads to apoptosis with green LED of 30mW with 30nm GNPs.